Pelatihan Pelaporan SPT Pemilik UMKM di Kelurahan Sendangguwo Kota Semarang - Maya Aresteria; Stacia Mege; Alfita Rakhamayani (Yayasan Sumber Daya Manusia Cerdas, 2023)
MSMEs have an important role in a country's economy because of their contribution to economic growth, job creation, innovation, and community empowerment. The establishment of Micro, Small and Medium Enterprises (MSMEs) creates an obligation in the field of taxation. Businesses or business owners are obliged to pay taxes and submit notification letters. The problem that often occurs is that MSME actors do not fully understand tax obligations, including the obligation to submit SPT reports. Non-compliance with these obligations will result in sanctions for MSMEs. Administrative fines will be given when MSMEs are late or do not submit Periodic and Annual Tax Returns. The service team then carries out community service activities as a solution to the problems faced by MSME actors. The method used in this PKM is lecture, practice and discussion with a participatory approach. The lecture is carried out online with the meeting application. The practice is carried out by utilizing online SPT form technology with examples of various tax cases in the MSME environment. Discussions with MSME actors aim to develop new skills and approaches in solving problems encountered in SPT reporting. After the SPT reporting training activity in Sendangguwo Village, Tembalang District, MSME actors became more aware and were able to fill out SPT properly.